Audiovisual Media to Improve Football Passing Learning Outcomes among Elementary School Students: A Classroom Action Research - Abrar Abrar; Muh. Adnan Hudain; Ahmad Adil (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This study aimed to improve students' learning outcomes in the football passing technique through the application of audiovisual media among fifth-grade students at Elementary School Inpres Tallo Tua I, Makassar, Indonesia. The main problem addressed was the low psychomotor learning outcomes of students, most of whom had not reached the Minimum Mastery Criterion (Kriteria Ketuntasan Minimal, KKM = 75). A Classroom Action Research (CAR) design was employed, implemented in two cycles, each consisting of planning, action, observation, and reflection phases. The participants were all 31 fifth-grade students (17 boys and 14 girls), selected through total sampling. Data were collected through observation, performance tests, and documentation, and were analyzed descriptively using mastery-learning percentages. The results showed that the application of audiovisual media significantly improved students' passing performance. The classical mastery percentage increased from 64.52% in Cycle I (mean score = 73) to 96.77% in Cycle II (mean score = 88), exceeding the pre-determined success indicator of 85% classical mastery. This improvement indicates that audiovisual media enhanced students' comprehension, motivation, and motor skills in performing the inside-of-the-foot passing technique correctly. It can be concluded that audiovisual media is an effective instructional tool for improving football passing learning outcomes among elementary school students. This study implies that the use of innovative and engaging instructional media is essential for improving the quality of physical education in primary schools.